Chromosome‐level genome assembly of Dastarcus helophoroides provides insights into CYP450 genes expression upon insecticide exposure. Issue 4 (28th December 2022) - Zhang, Zhengqing; Pei, Pei; Zhang, Meng; Li, Feifei; Tang, Guanghui
Abstract: BACKGROUND: Dastarcus helophoroides is an important natural enemy of cerambycids, and is wildly used in biological control of pests. Nevertheless, the absence of complete genomic information limits the investigation of the underlying molecular mechanisms. Here, a chromosome‐level of Dastarcus helophoroides genome is assembled using a combination strategy of Illumina, PacBio, 10x™ Genomics, and Hi‐C. RESULTS: The final assembly is 609.09 Mb with contig N50, scaffold N50 and GC content of 5.46 Mb, 42.56 Mb and 31.50%, respectively, and 95.25% of the contigs anchor into 13 chromosomes. In total 14 890 protein‐coding genes and 65.37% repeat sequences are predicted in the assembly genome. The phylogenetic analysis of single‐copy gene families shared among 20 insect species indicates that Dastarcus helophoroides is placed as the sister species to clade (Nitidulidae+Curculionoidea+Chrysomeloidea) + Tenebrionoidea, and diverges from the related species ~242.9 Mya. In total 36 expanded gene families are identified in Dastarcus helophoroides genome, and are functionally related to drug metabolism and metabolism of xenobiotics by cytochrome P450. Some members of CYP4 Clade and CYP6 Clade are up‐regulated in Dastarcus helophoroides adults upon insecticide exposure, of which expressions of DhCYP4Q, DhCYP6A14X1 and DhCYP4C1 are significantly up‐regulated. The silencing of the three genes leads to adults more sensitive to insecticide and increased knocked‐down rate, which may indicate their critical roles in stress resistance and detoxication. CONCLUSION: Our study systematically integrated the chromosome‐level genome, transcriptome and gene expression of Dastarcus helophoroides, which will provide valuable resources for understanding mechanisms of pesticide metabolism, growth and development, and utilization of the natural enemy in integrated control. © 2022 Society of Chemical Industry. Abstract : A chromosome‐level of Dastarcus helophoroides genome is assembled and provides genomic information for research on its molecular mechanisms. The expression profile of CYP450 genes are identified based on transcriptome and gene silencing of adult Dastarcus helophoroides upon insecticide exposure.